Targeted risk assessment for prochloraz - European Food Safety Authority (EFSA) (EFSA Journal, 2023)
Abstract In accordance with Article 43 of Regulation (EC) No 396/2005, the European Commission requested EFSA to prepare a statement with a targeted risk assessment for prochloraz. Based on the data available, EFSA performed an acute exposure assessment for EU consumers for the existing EU maximum residue levels (MRLs) based on codex maximum residue limits (CXLs) and identified possible risk for consumers for the CXLs on granate apples and papaya.